Answer:
around 228
Step-by-step explanation:
Answer:
Neither even nor odd
Step-by-step explanation:
The graph of y = -5x^2 - 2x + 6 is that of a parabola that opens down. This function is neither even nor odd because a point chosen at random is neither reflected in the y-axis nor reflected in the origin.
Answer:
3
Step-by-step explanation:
11g - 9k + 3
Let g = 9 and k =11
11 * 9 - 9*11 +3
Multiply
99 - 99 +3
Add
3
Answer:
x = 0
Step-by-step explanation:
6 - 2x = 6x - 10x + 6
1. Isolate the variable (x)
6 - 2x = 6x - 10x + 6 -> 6 = 6x - 10x + 2x + 6
- Subtract 6 from both sides
6x - 10x + 2x + 6 -> 0 = 6x - 10x + 2x
2. Combine like terms
0 = 6x - 10x + 2x -> 0 = -2x
3. Solve
0 = x
*Note: 0 divided by anything is 0 so 0/-2 is 0
(unless it is 0/0 which equals 1)
Answer:

Step-by-step explanation:
You can see the attached picture